Skrining Aspergillus Antagonis Terhadap Phythophthora palmivora Butler. Penyebab Penyakit Busuk Buah Kakao di Sulawesi Tengah - Fitriani Husain; Umrah Umrah; Muhammad Alwi (Biocelebes, 2012)
The study about “Screening of Aspergillus antagonistic to Phytopthora palmivora causing black pod disease of cocoa at Sulawesi Tengah” has been carried out during three months. The purpose of this study is how to getting the best of local isolats of Aspergillus sp. antagonistic that can be controlling of Phytopthora palmivora. The method of this study is exploring the local Aspergillus fungi as biological control of the P. palmivora causing black pod disease of cocoa in five Districts central of production kakao, such as Donggala District, Parigi Moutong, Poso, Morowali, and Buol. Parameter observed were antagonist test in vitro and pra in vivo on the cocoa. The result of this study was obtained fourteen isolats of Aspergillus sp namely are (1) Poso District: L-1, L-2, L-3 ; (2) Morowali District, L-4, L-5, L-6; (3) Donggala District, L-7, L-8, L-9; (4) Parimo District , L-10, L-11, L-12; (5) Buol District, L-13, L-14. All isolates of Aspergillus sp. were antagonistic in vitro on P. palmivora, but only six isolates, namely are L-1, L-10, L14, L-4, L-6, dan L-8 were have the best ability to controlling P. Palmivora on the cocoa pod. Key words: Aspergillus sp., antagonism, Phytophthora palmivora and Cocoa pod.